Development of an antibody technique for acetylcholinesterase expression detection in the gill of Nile tilapia (Oreochromis niloticus) as a glyphosate-based herbicide biomarker - Phochit Nanthanawat; Pongpat Kiatprasert; Amnuay Wattanakornsiri; Jakkaphun Nanuam; Witchuda Prasatkaew; Sawipa Ruttanakorn; Chutima Thanomsit (Toxicology Reports, 2022)
Widely used glyphosate-based herbicides can remain in agricultural fields or be spread into the surrounding environment. This study aimed to develop an antibody technique for assessing acetylcholinesterase (AChE) expression in Nile tilapia (Oreochromis niloticus) after glyphosate exposure in the assessed tissues consisting of plasma, muscle, gills, and liver. Results showed that the cumulative mortality of fish exposed to glyphosate increased with exposure time and glyphosate concentration. The LC50 was evaluated using probit analysis. A sub-lethal concentration of 2 µL L−1 glyphosate-based herbicide altered behavioural and physiological appearances. AChE expression decreased compared to that in the control group with increasing glyphosate exposure time. The 71 kDa AChE was consecutively expressed in plasma, muscle, gill, and liver under laboratory and field conditions, as detected by dot blot and Western blot analysis. Furthermore, laboratory and field studies of the gills showed positive immunohistochemical results. Although this study could detect AChE expression in many tissues, using gills to assess AChE exposure allowed the fish not to be sacrificed compared with other organ studies, and this technique can be used in both laboratory and field conditions. In conclusion, the antibody technique can be applied to measure AChE expression in the gill tissue to assess glyphosate-based herbicide exposure.